Online harms: Problematic technology use is a public health concern and requires a multistakeholder approach - Daria J. Kuss (Addictive Behaviors Reports)
Modern technologies are inherently ubiquitous and mobile, making internet use the status quo. As our daily lives become increasingly mediated, social media have become ways of being and relating and impact on what we do and who we are. Despite the numerous benefits technology use offers to users, there is accumulating empirical evidence suggesting that problematic technology use is associated with online harms, which can impact the users’ mental health and wellbeing detrimentally. Online harms are a public health concern and must be addressed from a multistakeholder perspective, engaging governments, parents, schools, the industry, and healthcare services on an international scale. Governments are working on improving user safety, parents are calling for support by educational establishments to prevent online harms, whilst the technology industry is advised to increase their corporate social responsibility efforts. Meanwhile, healthcare services must be accessible to provide professional support for those affected.